A partial agonist for retinoid X receptor mitigates experimental colitis. (26th December 2018) - Onuki, Masayoshi; Watanabe, Masaki; Ishihara, Narumi; Suzuki, Koichiro; Takizawa, Kei; Hirota, Masato; Yamada, Takahiro; Egawa, Aiko; Shibahara, Osamu; Nishii, Midori; Fujihara, Michiko; Makishima, Makoto; et al.
Abstract: Inflammatory bowel disease (IBD), including ulcerative colitis and Crohn's disease, is an intractable disease of the gastrointestinal tract. Multiple environmental factors, including food ingredients, have been implicated in the development of these diseases. For example, animal fat-rich diets are predisposing factors for ulcerative colitis, whereas n -3 unsaturated fatty acids such as docosahexaenoic acid (DHA) show protective effects in experimental colitis and are negatively correlated with the incidence of ulcerative colitis and Crohn's disease. Given that DHA exhibits agonistic activity on retinoid X receptor (RXR), activation of RXR could be a therapeutic strategy for IBD. However, conventional full RXR agonists are known to show considerable adverse effects. We therefore took advantage of a partial RXR agonist, CBt-PMN, to minimize the adverse effects, and evaluated its efficacy in dextran sodium sulfate-induced colitis. Administration of CBt-PMN efficiently ameliorated the symptoms of colitis. This effect was attributed to the down-regulation of pro-inflammatory cytokines such as Tnf and Il6 in colon-infiltrating monocytes. Down-regulation of pro-inflammatory cytokines by CBt-PMN was also evident in lipopolysaccharide-stimulated bone marrow-derived macrophages (BMDMs). Among many RXR-associated nuclear receptors, activation of peroxisome proliferator-activated receptor δ (PPARδ) and nuclear hormone receptor 77 (Nur77) suppressed cytokine production by BMDMs. These observations suggest that the activation of PPARδ/RXR and Nur77/RXR heterodimers by CBt-PMN through the permissive mechanism is responsible for diminishing the monocyte-mediated inflammatory response in the gut. Our data highlight the importance of RXR activation in the regulation of colitis. Abstract : A partial RXR agonist reduces side-effects while ameliorating colitis